Development and screening of EMS mutants with altered seed oil content or fatty acid composition in Brassica napus. (23rd November 2020) - Tang, Shan; Liu, Dong‐Xu; Lu, Shaoping; Yu, Liangqian; Li, Yuqing; Lin, Shengli; Li, Long; Du, Zhuolin; Liu, Xiao; Li, Xiao; Ma, Wei; Yang, Qing‐Yong; et al.
SUMMARY: Brassica napus is an important oilseed crop in the world, and the mechanism of seed oil biosynthesis in B. napus remains unclear. In order to study the mechanism of oil biosynthesis and generate germplasms for breeding, an ethyl methanesulfonate (EMS) mutant population with ~100 000 M2 lines was generated using Zhongshuang 11 as the parent line. The EMS‐induced genome‐wide mutations in M2−M4 plants were assessed. The average number of mutations including single nucleotide polymorphisms and insertion/deletion in M2−M4 was 21 177, 28 675 and 17 915, respectively. The effects of the mutations on gene function were predicted in M2−M4 mutants, respectively. We screened the seeds from 98 113 M2 lines, and 9415 seed oil content and fatty acid mutants were identified. We further confirmed 686 mutants with altered seed oil content and fatty acid in advanced generation (M4 seeds). Five representative M4 mutants with increased oleic acid were re‐sequenced, and the potential causal variations in FAD2 and ROD1 genes were identified. This study generated and screened a large scale of B. napus EMS mutant population, and the identified mutants could provide useful genetic resources for the study of oil biosynthesis and genetic improvement of seed oil content and fatty acid composition of B. napus in the future. Significance Statement: Seed oil content and fatty acid composition are important traits of oil crop Brassica napus . In this study, a large number of Brassica napus EMS mutants with altered seed oil content or fatty acid composition have been generated and identified. This study provides useful genetic resources for functional genomics study and genetic improvement of B. napus .